A mediating effect of business growth on zakat empowerment program and mustahiq's welfare - Tika Widiastuti; Ilmiawan Auwalin; Lina Nugraha Rani; Muhammad Ubaidillah Al Mustofa (Cogent Business & Management, 2021)
Zakat is an instrument of Islamic economic and social funds that contributes to the achievement of people wellbeing. This study examines the business growth as a mediating variable on the relationship between the impact of the zakat empowerment programs and mustahiq's (zakat recipient) welfare. This quantitative study employs Partial Least Square Structural Equation Modelling (PLS-SEM) analysis on 100 mustahiqs from different zakat empowerment programs in East Java and DI Yogyakarta. Zakat empowerment positively affects mustahiq's welfare. This indicates that the empowerment program successfully increases mustahiqs' wellbeing and their business. Business growth as a mediating variable on the relationship between business assistantship and mustahiq welfare also shows a positive and significant effect. Further, macroeconomic indicators consisting of GRDP and inflation and internal factors consisting of age and educational level, have different impacts on the business growth of mustahiq. This study confirms the zakat empowerment program's role in improving the mustahiq's welfare based on maqashid al-shariah (the Islamic objectives). Zakat community empowerment is a solution to suppress the poverty rate and possible for reducing inequality and ending poverty in Indonesia. This study extends the literature by providing a unique measurement of mustahiq welfare. This study incorporates maqashid al-shariah considerations to measure the wellbeing.
Keywords: I30; 650; productive zakat; empowerment; poverty alleviation; welfare